English Teacher’s Strategies in Teaching Vocabulary to Young Learners at Elementary Level An-Nahl Jambi - Annajmi, Annajmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The purpose of this study was investigating English teachers’ strategies and also the dominant strategies used by English teachers in teaching vocabulary to young learners at Elementary Level An-Nahl Jambi. The subject of this study was an English teacher at Elementary Level An-Nahl Jambi. The investigation of this study was done through qualitative method with observation and interviews. The observation checklist, interview protocol, and video recorder were used as instruments for this study. The observation was done once in grade two which consists of three classes and the interview was done approximately 30-60 minutes two times. The findings of this study showed that there were five strategies used by teachers in teaching English vocabulary to young learners at Elementary Level An-Nahl Jambi. They were games, small groups, role-play, brainstorming, and demonstration. There were also the dominant strategies used by the teacher in teaching vocabulary to young learners are games and small groups.